2022
DOI: 10.1111/1755-0998.13703
|View full text |Cite
|
Sign up to set email alerts
|

Extracting abundance information from DNA‐based data

Abstract: The accurate extraction of species‐abundance information from DNA‐based data (metabarcoding, metagenomics) could contribute usefully to diet analysis and food‐web reconstruction, the inference of species interactions, the modelling of population dynamics and species distributions, the biomonitoring of environmental state and change, and the inference of false positives and negatives. However, multiple sources of bias and noise in sampling and processing combine to inject error into DNA‐based data sets. To unde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 142 publications
0
35
0
Order By: Relevance
“…How well species abundance may be estimated through metabarcoding is currently a hotly debated topic. Early studies suggested that metabarcoding was unsuitable for quantification, but more recent efforts using correction factors or spike‐ins of known concentration to calibrate metabarcoding‐based estimates have reported encouraging results (Ershova et al, 2021; Luo et al, 2023). Nevertheless, our study offers some of the first quantitative analyses of the accuracy that might be achieved using such approaches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…How well species abundance may be estimated through metabarcoding is currently a hotly debated topic. Early studies suggested that metabarcoding was unsuitable for quantification, but more recent efforts using correction factors or spike‐ins of known concentration to calibrate metabarcoding‐based estimates have reported encouraging results (Ershova et al, 2021; Luo et al, 2023). Nevertheless, our study offers some of the first quantitative analyses of the accuracy that might be achieved using such approaches.…”
Section: Discussionmentioning
confidence: 99%
“…One of the solutions proposed to address these challenges is the introduction of known amounts of either tissue or DNA (so-called spike-ins; Ji et al, 2020;Luo et al, 2023;Thomas et al, 2016) to facilitate normalizing sequencing results between and within samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative sample preparations have been suggested to facilitate a posteriori morphological control, such as the removal of legs (Braukmann et al 2019) which is timeconsuming, or photographing bulk specimens which is a more scalable process but may be insufficient for accurate morphological identification. As for abundance information, optional molecular steps such as DNA spike-in of known mock communities and DNA concentration can also be implemented to infer taxa relative abundance from sequence read-based number correction (Luo et al 2022). Non-destructive DNA extraction buffer (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Given such uncertainty, the conservative interpretation has been to treat metabarcoding data as presence/absence until evidence for reliable correction factors can be obtained (Pawlowski et al, 2018). However, correction factors only allow changes in the relative abundance within a taxon to be estimated (Luo et al, 2022), and the prospect of calibrating for bias (McLaren et al, 2019) remains a distant prospect for those diverse communities where we gain most from DNA‐based identification.…”
Section: Introductionmentioning
confidence: 99%